PENEGAKAN HUKUM TINDAK PIDANA PENGGELAPAN BARANG ELEKTRONIK JENIS LAPTOP TERHADAP PASAL 36 UNDANG-UNDANG NOMOR 42 TAHUN 1999 TENTANG JAMINAN FIDUSIA DI PT. ADIRA QUANTUM MULTIFINANCE TASIKMALAYA: Array - Herdi Wibowo; Eka Jaenal Arifin; Arif Hermawan; Sirrinawati Sirrinawati (Case Law : Journal of Law, 2020)
In reality on the ground, many people who take leasing goods embezzled the goods which were the objects of the leasing and contradicted the existing regulations. In this study the authors formulated the problem to what extent law enforcement criminal acts of embezzlement of electronic goods of laptop types against Article 36 of Law Number 42 of 1999 concerning Fiduciary Guarantees at PT. Adira Quantum Multifinance Tasikmalaya; constraints and efforts. The method used in this study is a descriptive analytical method, which is a way to solve problems or answer the problems being faced, carried out by way of collecting, classification, data analysis concluded with the aim to make a picture of a situation objectively, with a juridical approach method normative. Based on the results of the study it can be concluded that law enforcement of the embezzlement of electronic goods of laptop types against article 36 of Law Number 42 of 1999 Concerning Fiduciary Guarantees at PT. Adira Quantum Multifinance Tasikmalaya is not implemented in accordance with the provisions of article 36 of Law Number 42 of 1999 concerning Fiduciary Guarantees. The constraints are the existence of goods which are used as fiduciary collateral is no longer in the hands of the debtor and is in a third party that cannot be traced to its existence, still found incomplete administrative requirements of goods which are the object of fiduciary collateral at issue by the finance company, and requires time long time in taking or executing goods that are guaranteed. Efforts are to forcibly take / confiscate electronic goods in the form of laptops and report them to the police, because the company has been unable to take action against the debtor, because the debtor is difficult to find or cannot show / surrender the goods as collateral.